2021
DOI: 10.1186/s13750-021-00237-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the impacts of chemicals arising from human activity on tropical reef-building corals; a systematic map

Abstract: Background Tropical coral reefs cover ca. 0.1% of the Earth’s surface but host an outstanding biodiversity and provide important ecosystem services to millions of people living nearby. They are currently threatened by local stressors (e.g. nutrient enrichment and chemical pollution arising from poor land management, sewage effluents, agriculture, industry) and global stressors (mainly seawater warming and acidification, i.e. climate change). Global and local stressors interact in different ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(34 reference statements)
0
10
0
1
Order By: Relevance
“…To know the status of the available literature on this topic, the first step was to create a systematic map of the effects of chemicals arising from human activities on tropical reef-building corals. The systematic map was published in the Environmental Evidence Journal in 2021 [34]. A large amount of scientific literature was found (908 articles, 7,937 studies -up to March 2020) and four relevant knowledge clusters were identified: (1) evidence on chemical bioaccumulation by corals (2050 studies); (2) evidence on the effects of nutrient enrichment on corals (2496 studies); (3) evidence on the effects of human activities on corals without reference to specific chemicals (1127 studies); and (4) experimental evidence on the ecotoxicological effects of chemicals on corals (other than nutrient enrichment, 2007 studies).…”
Section: Topic Identification and Stakeholder Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…To know the status of the available literature on this topic, the first step was to create a systematic map of the effects of chemicals arising from human activities on tropical reef-building corals. The systematic map was published in the Environmental Evidence Journal in 2021 [34]. A large amount of scientific literature was found (908 articles, 7,937 studies -up to March 2020) and four relevant knowledge clusters were identified: (1) evidence on chemical bioaccumulation by corals (2050 studies); (2) evidence on the effects of nutrient enrichment on corals (2496 studies); (3) evidence on the effects of human activities on corals without reference to specific chemicals (1127 studies); and (4) experimental evidence on the ecotoxicological effects of chemicals on corals (other than nutrient enrichment, 2007 studies).…”
Section: Topic Identification and Stakeholder Inputmentioning
confidence: 99%
“…The evidence was taken from the published systematic map of the impact of chemicals derived from human activities on tropical reef-building corals [34]. For the map, literature was searched in two bibliographic databases (Scopus and Web of Science Core Collection, March 19, 2020), three search engines (CORE, July 7, 2020, Google Scholar and GreenFile, July 8, 2020), two dissertations repositories (September 15, 2020), 11 specialist websites (from April 21 to May 29, 2020) and a call for literature (July 13, 2020).…”
Section: Searching For Articlesmentioning
confidence: 99%
“…This review seeks to systematically assess the existing body of evidence relating upwelling to benthic community structure on coral reefs and to provide a policy-neutral summary of existing evidence. Systematic reviews linking reef health with anthropogenic stressors including pollution [ 36 ], sediment exposure [ 37 ], chemical pollutants [ 38 ] and anthropogenic nutrient enrichment [ 39 ] have provided valuable overview analysis of the state of evidence. Such broad evidence synthesis allows policy makers and reef managers to make informed, evidence-based decisions founded in robust science.…”
Section: Introductionmentioning
confidence: 99%
“…Фталаты (сложные эфиры о-фталевой кислоты) обнаруживаются в окружающей среде практически повсеместно: в сточных водах, почве, воздухе, продуктах питания [1][2][3][4][5][6]. На сегодняшний день имеются две концепции, рассматривающие появление фталатов в окружающей среде и их влияние на живые организмы.…”
Section: Introductionunclassified